(untitled) (Third Sector Social Economic Review, 2019)
Universities influence the economic, social and cultural structures of cities they are in. The expenditure ranges of university students form an aspect of the assessment of the contribution made for urban economics. In the scope of this study, a questionnaire was conducted to the Students of Hitit University Faculty of Economics and Administrative Sciences (FEAS), to measure the reflections of their expenditures for the economy of Corum Province. In the study, it was determined that the students attending the questionnaire had spent an average of 630 TL per month. Accordingly, the students receiving education at FEAS in the period of 2016-2017 made a contribution of approximatel 18,9 million TL to the economy of Corum Province, with their expenditures, during one year of education period. When this approximately found amount of expenditure is generalized for all university students, it yields an amount of expenditure nearly 105 million TL. Except for the institutional expenditures of the university and individual expenditures of the university staff it can be said that the students alone make a great contribution to the city economy. It has been concluded that when revenue and expenditure items and accommodation preferences are considered together, the contribution made by students to the city has been largely encouraged by opportunies such as student residences and scholarships, offered by the state for students. When considered from this aspect, educational supports, as well as offering an indirect contribution to the urban economics, also do an important socialization duty for a large part of university students, who cannot sustain university education with their own financial possibilities.